(untitled) (Desenvolvimento em Questão, 2026)
This paper aims to present the Environmental, Social, and Governance (ESG) approach in the global Oil and Gas (O&G) industry through a systematic review of the literature based on the recommendations of the PRISMA Group, which resulted in the analysis of 32 scientific articles from the 312 articles identified up to 2024. The first was published in 2004, and 70% of the others were published from 2020 onwards, confirming the contemporary nature of the topic, with co-authorship being the predominant form. The related fields of Corporate Social Responsibility (CSR) and ESC constituted the theoretical framework for the vast majority of articles in different journals. The O&G industry was analyzed in developed and developing countries with an emphasis on environmental and governance aspects rather than social aspects. Broader issues such as the role of states, policies, environmental regulation, technologies, and international recommendations were also addressed. The articles were based on bibliographic and documentary research, with emphasis on the use of sustainability reports and company databases with statistical treatment. Field research supported by questionnaires, interviews, and direct observation was also identified. The results showed the consolidation of the ESG agenda in the global O&G industry in the diversity observed.